Thermal Characterization of Resin Concrete Elaborate By Infusion (International Journal of Scientific Research and Management (IJSRM), 2021)
This paper presents the results of numerical simulation to investigate the effect of temperature on the performance of resin concrete. Resin concrete is a composite material in which polymeric materials are used to bond the aggregates in a fashion similar to that used in the preparation of cement concrete. In this paper, at first the temperature distribution in gravel preform heated with epoxy resin injection was investigated. Furthermore, a thermo-mechanical study is presented. For this purpose, prismatic and cylindrical specimens were prepared for flexural and compressive tests, respectively, at different temperatures. The effect of heating on the thermal conductivity and elastic modulus were evaluated. Finally, the thermal behavior of resin concrete has been compared to that of cement concrete. When exposed to high temperatures the epoxy polymer concrete shows a significant loss of strengths mainly due to the thermo-oxidative degradation of the epoxy polymer and to the debonding between aggregates and the binder. Results show that when exposed to temperatures less than 250°C the epoxy polymer concrete is still more efficient than cement based concrete.